2021
DOI: 10.1007/s00330-021-07786-0
|View full text |Cite
|
Sign up to set email alerts
|

Threshold-dependent iodine imaging and spectral separation in a whole-body photon-counting CT system

Abstract: Objective To evaluate the dual-energy (DE) performance and spectral separation with respect to iodine imaging in a photon-counting CT (PCCT) and compare it to dual-source CT (DSCT) DE imaging. Methods A semi-anthropomorphic phantom extendable with fat rings equipped with iodine vials is measured in an experimental PCCT. The system comprises a PC detector with two energy bins (20 keV, T) and (T, eU) with threshold T and tube voltage U. Measurements using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Finally, as previously said, the PCD-CT system offers 3 different scan modes that were evaluated in the current study: the HR-mode (a micropixel mode, currently used at 120 kVp and optimized for lung imaging on non–contrast-enhanced CT) and the 2 Quantum modes (Q and Q+). Although the HR-mode is best for lung imaging on noncontrast CT, the latter 2 have their biggest advantages in contrast enhanced CT, because these modes allow for spectral imaging 49–53 . In this current study on non–contrast-enhanced CT, spectral imaging played a minor role.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Finally, as previously said, the PCD-CT system offers 3 different scan modes that were evaluated in the current study: the HR-mode (a micropixel mode, currently used at 120 kVp and optimized for lung imaging on non–contrast-enhanced CT) and the 2 Quantum modes (Q and Q+). Although the HR-mode is best for lung imaging on noncontrast CT, the latter 2 have their biggest advantages in contrast enhanced CT, because these modes allow for spectral imaging 49–53 . In this current study on non–contrast-enhanced CT, spectral imaging played a minor role.…”
Section: Discussionmentioning
confidence: 69%
“…Although the HR-mode is best for lung imaging on noncontrast CT, the latter 2 have their biggest advantages in contrast enhanced CT, because these modes allow for spectral imaging. [49][50][51][52][53] In this current study on non-contrast-enhanced CT, spectral imaging played a minor role.…”
Section: Discussionmentioning
confidence: 84%
“…The spectral distortion was included in Equation ( 1) as described by Schlomka et al, 11 and it was used to generate the theoretically expected photon counts for each energy bin and calculate the likelihood. The following fan-beam geometry was considered to mimic an existing PCD-CT system [44][45][46] : The distance from source to center was 59.5 cm, the center to detector 49 cm, and the PCD with 0.9-mm detector pitch. The total number of views was 1000 per 2𝜋.…”
Section: Scan Conditionsmentioning
confidence: 99%
“…This study demonstrated that PCD technology produces higher‐quality images at lower doses, but it was not quantitative in the sense that VMI levels were not compared. Liu et al 28 . provided a quantitative evaluation of multiple VMI levels between DE‐CT and PC‐CT Siemens scanners at low doses, reporting improved accuracy in a large phantom and a significant reduction in electronic background noise.…”
Section: Introductionmentioning
confidence: 99%